METHODOLOGICAL APPROACHES TO FORENSIC IDENTIFICATION OF SIM CARD MOBILE PHONES - G. Khanina (Теория и практика судебной экспертизы, 2014)
The paper looks at various methodological approaches that can be used by forensiccommodity examiners to identify mobile phones with SIM cards.